2016
DOI: 10.3892/ol.2016.5263
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin specific protease 21 upregulation in breast cancer promotes cell tumorigenic capability and is associated with the NOD-like receptor signaling pathway

Abstract: Ubiquitination and deubiquitination have emerged as critical regulators in cancer. In the present study, the expression pattern of 50 ubiquitin-specific proteases (USPs) was summarized in breast cancer using a bioinformatics approach, and USP21 was identified as the most altered gene in breast cancer. In particular, expression of USP21 in triple negative breast cancer (TNBC) cell lines was greater compared with other subtypes of breast cancer. Knockdown of USP21 in TNBC cells inhibited cell proliferation, migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
(44 reference statements)
1
20
1
Order By: Relevance
“…USP21 amplification was also observed in several other cancer types ( Fig. 1B), which is consistent with previous reports that USP21 regulates cell proliferation and metastasis in bladder cancer (Chen et al 2017), hepatocellular carcinoma Li et al 2018), triple-negative breast cancer and renal cell carcinoma (Peng et al 2016). However, there were no molecular mechanistic insights as to whether and how USP21 may contribute to oncogenesis.…”
Section: Usp21 Is Highly Amplified In Pdacsupporting
confidence: 89%
“…USP21 amplification was also observed in several other cancer types ( Fig. 1B), which is consistent with previous reports that USP21 regulates cell proliferation and metastasis in bladder cancer (Chen et al 2017), hepatocellular carcinoma Li et al 2018), triple-negative breast cancer and renal cell carcinoma (Peng et al 2016). However, there were no molecular mechanistic insights as to whether and how USP21 may contribute to oncogenesis.…”
Section: Usp21 Is Highly Amplified In Pdacsupporting
confidence: 89%
“…USP21 was reported to play a tumor promoting role in some cancers. For example, knockdown of USP21 cells can dampen cell growth, migration, and invasion in triple‐negative breast cancer (TNBC) . In present study, we investigated its expression and found that it was also up‐regulated in OSCC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 75%
“…For example, knockdown of USP21 cells can dampen cell growth, migration, and invasion in triple-negative breast cancer (TNBC). 22 In present study, we investigated its expression and found that it was also up-regulated in OSCC tissues and cell lines. USP21 silencing can attenuate cell growth, migration, and invasion, but promoting cell apoptosis.…”
Section: Discussionmentioning
confidence: 79%
“…ESCC samples were flash frozen in liquid nitrogen and homogenized with a mortar and pestle, as previously described. 17 , 18 , 19 Total RNA was extracted using TRIzol (Invitrogen, China). 20 Quantitative RT-PCR was performed as previously described.…”
Section: Methodsmentioning
confidence: 99%